A estética da fome em Rio, 40 graus e a cosmética da fome em Cidade de Deus - Prado, Antônio Teixeira do (2007)
In the article “From Esthetics to Cosmetics of Hunger” in the newspaper “Jornal do Brasil-2001”, the researcher Ivana Bentes defends the idea that the national movies are retaking themes about misery and violence not as form of social revealing to unmask the Brazilian society but in order to treat about the' Cosmetic of hunger', which misery and violence are showed as entertainment and it appears from submissive, trite and trivial. Bentes also points out that the inlanders from the countryside in Brazil are being substituted from slum and disadvantage people and unaware of urban Brazil, that is, an idea in the head and a camera in the hand; a body to body with reality-it becomes the steadecam, the camera that surfs over the reality, an empty discourse mark that values the beauty and the quality of image. That’s why she says there is a change of esthetics as cosmetics of hunger in Brazilian films. So, this work aims at verifying if there is a change of esthetics as cosmetics of hunger can be found in Rio, 40 Graus (1955) film, by Nelson Pereira dos Santos and the City of God (2002), by Fernando Meireles. Both films reveals poverty in slum and black children who are victims of violence and social exclusion. The former (which is in postmodern) was taken place in Morro do Cabuçu, where five boys go into town to sell peanut in the main tourists places on a Sunday Summer. The latter was taken place in God of City (neighborhood), where children attempt the traffic of drug. Rio, 40 Graus is considered the first film that reveals some social problems mentioned above, according to the new-realism practice, that is to say, non-actors played in the film. This also happened to God of City